Severe psittacosis progressing to suspected organizing pneumonia and the role of corticosteroids. (2021) - Zuzek, Rachael; Green, Malcolm; May, Stephen
Abstract: Background: Psittacosis is a systemic disease usually with respiratory involvement, caused by the obligate intracellular bacterium Chlamydia psittaci . Exposure to birds, the main zoonotic reservoir, is a major risk factor for infection. The spectrum of disease is highly variable, ranging from subclinical infection to severe pneumonia requiring mechanical ventilation. There is limited data on psittacosis progressing to organizing pneumonia and management of such cases. Case presentation: A 63-year-old man was referred to a rural hospital with 11 days of fevers to 39 °C, myalgia, lethargy and several days of dry cough. After initial treatment with benzylpenicillin and doxycycline for left lower pneumonia found on CXR, the patient deteriorated with extensive bilateral consolidation on chest CT requiring mechanical ventilation. Atypical pneumonia screening was negative, however, exposure to a sick bird prior to symptom onset triggered testing for C. psittaci which was positive. Doxycycline was recommenced with minimal benefit, and organizing pneumonia was later suspected. The patient slowly improved with a weaning course of corticosteroids started after 19 days and was discharged from hospital. He unfortunately was re-admitted and died several months later. Conclusion: Severe pneumonia is a rare, but potentially life-threatening complication of psittacosis. We present a case of psittacosis which progressed to suspected organizing pneumonia despite appropriate antibiotics, and subsequent treatment with corticosteroids. This case suggests it may be useful to consider corticosteroids early in therapy for patients with severe psittacosis. Our paper underlines the need for further research to determine the best management of severe psittacosis to improve patient outcomes.